2010 Second International Conference on Networks Security, Wireless Communications and Trusted Computing 2010
DOI: 10.1109/nswctc.2010.122
|View full text |Cite
|
Sign up to set email alerts
|

Security Evaluation for Wireless Network Based on Fuzzy-AHP with Variable Weight

Abstract: This paper proposes a wireless network security evaluation method based on Fuzzy-AHP (Analytic Hierarchy Process) with variable weight. In this paper, we first design the evaluation index system based on characteristics of wireless networks, and then analyze each uncertainty measured by the Fuzzy-AHP method, and introduce variable weight theory into Fuzzy-AHP method to address the difficulty of weight decision, overcome the subjectivity of weight decision to some extent and improve the accuracy of evaluation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…The parameter α is essential for the emphasizing weighting amplifier and directly affects the amplification intensity. According to a previous study [44], positive, negative and constant α values represent encouraging, punishing and constant amplification, respectively. In our implementation, we retain the SCs with a low score value and disregard those with a high score value; then, α becomes negative.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The parameter α is essential for the emphasizing weighting amplifier and directly affects the amplification intensity. According to a previous study [44], positive, negative and constant α values represent encouraging, punishing and constant amplification, respectively. In our implementation, we retain the SCs with a low score value and disregard those with a high score value; then, α becomes negative.…”
Section: Methodsmentioning
confidence: 99%
“…Hence, we revise the aforementioned variable weighting calculation [44] and propose an emphasizing weighting amplifier to resolve the weighting‐dilution problem. A new weighting vector, called variable weighting vector truebold-italicω^false(Xfalse), is calculated with Equation (14).…”
Section: In‐practice Revisionsmentioning
confidence: 99%
“…Expert opinion using the Delphi technique was used for pairwise comparisons. Finally, Zhang et al [58] used a combination of FAHP and variable weight Cyber Security Attacks, vulnerabilities, and penetration testing [30] Cyber Security Vulnerabilities, threats, users, protection mechanisms. encounters [31] Cyber Security Skills Soft skills, technical skills, certifications [32] System Security Controls Effectiveness, risk, budgetary constraints, exploitation, maintenance, mitigation time Information Security [33] Information Loss Security Human dependent, technical, random [34] Security Investments Confidentiality, data integrity, availability…”
Section: A Using Ahp To Assess Securitymentioning
confidence: 99%
“…[54] Security Level Agreements Compliance, data governance, information security Network Security [55] Network Security Assets, access control, communication [56] Smart Grid Security Smart terminal, wireless channel, password security, app. code, embedded system [57] Network Security Software, hardware, information, communication, organization, physical environment [58] Wireless Security Authenticity, availability, confidentiality, integrity, non-repudiation theory to assess wireless network security using the top-level criteria of authenticity, availability, confidentiality, and integrity. A case study suggested that the FAHP variableweight technique for assessing wireless network security was both efficient and practical.…”
Section: A Using Ahp To Assess Securitymentioning
confidence: 99%